Análise de vigas treliçadas de aço para aplicação em pontes - Criado, Tayla Castilho [UNESP] (2017)
The beams of modular truss bridge mades with steel are efficient alternatives when it is necessary to reach longs spans in the o buildingf bridges. They are usually used in bridges with structural beam system, both road bridges and railway. In many cases, there is the possibility of trusses are modular allowing fast construction or reconstruction, in cases of natural disasters, since the modules are produced ealier in the factory. Thus, this paper aims to make structural analysis of trusses of a road modular bridge, with modules of 3 meters long, considering the diagonals and the rakers in the form of "k" and trusses with diagonals in form of rhombus both bi- supported, with spans of 12 meters and 18 meters. The study was carried out considering the dead and live actions according to the Brazilian standards and the design of the structure was based on the NBR 8800: 2008. The results of the numerical analysis were compared with those obtained in the assay of the truss beam conducted in the laboratory civil-engineering NEPAE. In this way, it was concluded that the stress distributions vary according to the arrangement of the diagonals of the truss, that is, in the "LOSANGO" type truss, the influence of the stresses on these elements is greater than in the truss with diagonals in the form of "K". And so, the type of truss to be used consists of the diagonals and the amounts arranged in the form of "K", which was used for the scaling. Regarding the deformations and displacements, the structure presented an expected behavior, since the deformations match the forces that were received by each bar and that each of these forces is always inferior to the strength of the profile used for scalinh. Concluded that the structure did not reach the final and service boundary states and its behavior was satisfactory in face of the efforts to which it was submitted.